Accuracy of behavioral responses in early detection of autism spectrum disorders in children aged 18 months to 4 years with speech delay - Danu, Nugroho; Handryastuti, Setyo; Mangunatmadja, Irawan; Pusponegoro, Hardiono D. (Paediatrica Indonesiana, 2024)
Background Early detection of autism spectrum disorders (ASD) in children with speech delay is important to improve outcomes. Behavioral responses to calling, teasing, poking, and blocking can be used to screen for ASD in daily practice. Objective To evaluate the accuracy of behavioral responses to stimuli in detecting ASD in children aged 18 months to 4 years with speech delay. Methods This cross-sectional study was conducted in children with speech delay aged 18 months to 4 years who visited the Outpatient Clinic of Cipto Mangunkusumo Hospital, Jakarta. Subjects were stimulated while playing by poking, teasing, calling, and blocking (stopping the child’s play using the examiner’s hand) and were assessed for their responses. Lack of seeking eye contact with the examiner following the stimulus was considered as a response suggestive of ASD. Independent diagnosis based on DSM-V criteria was considered the gold standard to diagnose ASD or non-ASD. Results A total of 109 children were included in this study, with an average age of 32 (SD 7.4) months. There were 52 subjects (47.7%) with ASD and 57 subjects (52.2%) with non-ASD. Behavioral response analysis revealed that calling, blocking and teasing had high sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for identifying ASD. The poking response had the highest specificity to rule out ASD compared to other stimuli, with 75% sensitivity (95%CI 63.2% to 86.7%), 93% specificity (95%CI 86.3% to 99.6%), 90% PPV (95%CI 82% to 99.3%), and 80% NPV (95%CI 70.7% to 89.9%). When all behavioral responses were combined, with lack of a response to all four stimuli considered suggestive of ASD, we obtained 100% specificity, 42% sensitivity, 100% PPV and 65% NPV. Conclusion The combination of behavioral responses had high specificity, sensitivity, PPV, and NPV for early detection of ASD in children with speech delay.